2000
DOI: 10.1021/es9909879
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability to Earthworms of Aged DDT, DDE, DDD, and Dieldrin in Soil

Abstract: A study was conducted to determine the bioavailability of several pesticides that have persisted for various periods in soils in the field and the laboratory. Based on the concentrations or the percentages of the compound in soil samples that were found in the earthworm Eisenia foetida, ca. 30, 12, 34, and 20% of DDT, DDE, DDD, and a total of the three compounds were bioavailable in a soil treated in the field with DDT 49 years earlier. Only 28 or 43% of dieldrin aged for 49 years was bioavailable based on con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
3
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(119 citation statements)
references
References 30 publications
9
106
3
1
Order By: Relevance
“…Estimates of the half-life of DDT range from 2 -17 years (Extoxnet 1994), and that of DDE for 15 years. Nash and Woolsen (1967) found that 39% of an original application remained in soil 17 years later, while Morrison et al (2000) reported that 30% of DDT applied in one soil type 49 years earlier was still bio-available to earthworms. Setmire et al (1993) found DDE concentrations in biota from freshwater rivers and drains around the Salton Sea and Imperial Valley to be the highest documented in California, and ibis had some of the highest concentrations in birds from the valley.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the half-life of DDT range from 2 -17 years (Extoxnet 1994), and that of DDE for 15 years. Nash and Woolsen (1967) found that 39% of an original application remained in soil 17 years later, while Morrison et al (2000) reported that 30% of DDT applied in one soil type 49 years earlier was still bio-available to earthworms. Setmire et al (1993) found DDE concentrations in biota from freshwater rivers and drains around the Salton Sea and Imperial Valley to be the highest documented in California, and ibis had some of the highest concentrations in birds from the valley.…”
Section: Discussionmentioning
confidence: 99%
“…ablity by the formation of unextractable bound residues, 98,99) the uptake of pesticides even from the bound fraction of exhaustively extracted soils showed their partial release during digestion. 24,100,101) The EP theory has been successfully introduced to describe the bioaccumulation (BSAF) of pesticides in aquatic species, 30) while its application to the earthworm is still limited for polychlorinated aromatics and PAHs.…”
Section: Bioconcentration and Bioaccumulationmentioning
confidence: 99%
“…Alexander (2000) argued that because regulatory agencies do not take aging into account, toxic exposures are being over estimated in assessments and he cited his laboratory studies on earthworms in aged soils in support of his argument (Morrison et al 2000;Kelsey et al 2005). In contrast, Gaw et al (2012), studying the accumulation of DDE in Aporrectodea caliginosa in aged horticultural soils under laboratory conditions, concluded that DDE remains biologically available to earthworms and to animals that prey on earthworms.…”
Section: Introductionmentioning
confidence: 99%